Serotonin system in tunicates: insight from morphological and molecular approaches - Pennati, Roberta; Blumer, Giorgio; Mercurio, Silvia; Scarì, Giorgio (Frontiers in Ecology and Evolution, 2024)
Serotonin (5 hydroxytryptamine, 5-HT) is a biogenic amine of ancient origin that is widespread among animals. It plays multiple roles during development and in adults as neurotransmitter at synaptic level and neuro hormone controlling complex behaviors in both vertebrates and invertebrates. Tunicates occupy a key phylogenetic position to understand the evolution of serotonin functions since they are the sister group of vertebrates. The presence of serotonin in tunicates was first reported in adults of the ascidian Ciona robusta (formerly Ciona intestinalis) in the 1946. Since then, serotonin systems have been in many tunicate species and its functions during embryogenesis and metamorphosis explored. We reviewed the current knowledge about serotonin in these animals first by comparing its presence and localization in larvae and adults of different species. Then, we focused on the model organism Ciona for which data regarding sequences and expression patterns of genes involved in serotonin synthesis and function have been reported. Overall, we provided a comprehensive overview of serotonergic machinery in tunicates and gave hints for future studies in this field.